The impact of red and processed meat consumption on cancer and other health outcomes: Epidemiological evidences. (June 2016) - Boada, Luis D.; Henríquez-Hernández, L.A.; Luzardo, O.P.
Abstract: Meat is one of the staples of the human diet, which provides high-quality nutrients, but that also constitutes a relevant source of cholesterol and saturated fatty acids. Epidemiologic studies have linked consumption of red or processed meat with obesity, type 2 diabetes, cardiovascular diseases, and cancers. Most epidemiological studies suggest that a high intake of meat, especially processed meat, is associated with increased colorectal cancer risk. Potential reasons for the association between high meat intake and colorectal cancer risk include some chemicals naturally contained in meat, or generated by the processing and cooking. From the literature it can be concluded that there is enough epidemiological evidence linking processed meat intake and colorectal cancer risk, but there is limited evidence regarding unprocessed red meat intake and the disease. On the contrary, there is only limited evidence linking meat intake with other diseases such as cardiovascular disease, type 2 diabetes or other cancers. Nevertheless, the literature suggest that dietary intervention may be a promising approach for prevention of cancers of the colon, esophagus, liver, stomach and bladder, and type 2 diabetes and cardiovascular disease which still need to be confirmed by further well designed prospective studies and experimental research. Highlights: Red meat/processed meat intake is linked to colorectal carcinoma. Processed meat intake has been related to type 2 diabetes and cardiovascular disease. Meat intake have been associated to increased risk for other cancers. Decreased intake of meat may be a protective factor for several diseases. Enough evidence of the association between processed meat and colorectal cancer.